Chemical Exposure as Etiology in Developmental Origin of Adult Onset Human Cancer - Vähäkangas, Kirsi (Frontiers in Pharmacology, 2011)
Chemical exposures are in principle preventable causes of cancer. People are exposed to chemicals already during fetal period and the possibility of disturbances in human development by chemical compounds leading to cancer later in life has been proven by diethylstilbestrol. Involved mechanisms most probably include epigenetic modifications of promoter regions of key genes. The world-wide increases in cancer incidence and concurrent increase in the number and quantity of chemicals in the environment raises concerns about a link between these two. Developmental origin and related mechanisms in chemically-induced human cancer are worth pursuing.